Biobriket Dari Limbah Abu Batu Bara Sisa Pembakaran PLTU Dan Serbuk Penggergajian Kayu dengan Perekat Kertas Bekas - Myson Myson (Universitas Batanghari, 2020)
This research aims to reduce waste and process it into briquettes so that it produces energy that can be utilized by many people. Bottom ash from the rest of coal burning for PLTU, used paper from offices and education activities and sawdust along the banks of the Batanghari river, especially across the city of Jambi, are waste that will be utilized. The three initial compositions are determined to obtain the calories produced from the briquettes made. From the laboratory test results, it is obtained that heating values are in the range of 2500 to 2800 kcal / kg. These results are not satisfactory and still need to change the composition between sawdust, coal ash and waste paper in order to obtain a calorific value that corresponds to the calorific value produced by LPG gas.